(untitled) (Journal of Global Accounting, 2025)
This study examined the effect of cash control on the financial performance of listed agricultural firms in Nigeria over the period 2015 to 2024. Specifically, it investigated the effect of cash and cash equivalents, cash to book value, and cash conversion cycle, on return on assets (ROA) of five agricultural firms listed on the Nigerian Exchange Group. The study adopted a census sampling technique and employed an ex-post facto research design using secondary data obtained from the firms’ audited financial statements. Descriptive statistics were used to summarize the data, while panel regression analysis was conducted to test the hypotheses. The study found the following: cash to book value has a significant negative effect on ROA of listed agricultural firms in Nigeria (β = -0.2483; p = 0.0162); cash conversion cycle has a positive but insignificant effect on ROA of listed agricultural firms in Nigeria (β = 0.000030; p = 0.6133); cash and cash equivalents have a significant positive effect on ROA of listed agricultural firms in Nigeria (β = 0.0903; p = 0.0000). In conclusion, holding excessive cash relative to equity may be counterproductive, possibly signaling inefficient use of shareholder capital or a reluctance to reinvest idle funds into productive operations. The study recommends that Chief Financial Officers (CFOs) of agricultural firms should minimize idle cash relative to book value by channeling excess liquidity into value-adding investments that can improve asset productivity and enhance shareholder returns.